HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG TUMBUH KEMBANG TERHADAP PEMANFAATAN BUKU KIA OLEH IBU BALITA DI POSYANDU GAMPONG LEUHANKECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Marida Marida; Nanda Norisa; Lilis Suryani; Fitriani Fitriani (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
One way to monitor toddler growth and development is through the Maternal and Child Health Handbook (MCH Handbook). This handbook serves as an integrated monitoring tool that records a child's health and developmental status and can be used by families to independently maintain maternal and child health. The purpose of this study was to examine the relationship between knowledge and attitudes about growth and development and the use of the MCH Handbook by mothers of toddlers at the Gampong Leuhan Integrated Health Post (Posyandu), Johan Pahlawan District, West Aceh Regency. This research was an analytical survey using a cross-sectional approach. The population was 340 mothers who owned the MCH Handbook at the Gampong Leuhan Integrated Health Post (Posyandu), Johan Pahlawan District, West Aceh Regency. The sampling technique used the Solvin formula for 77 mothers with toddlers. The results showed a relationship between knowledge and attitudes about growth and development and the use of the MCH Handbook by mothers of toddlers at the Gampong Leuhan Integrated Health Post (Posyandu), Johan Pahlawan District, West Aceh Regency, with a probability value of 0.000 or <0.05. The conclusion of this study is that there is a Relationship between Knowledge and Attitudes about Growth and Development and the Use of KIA Books by Toddler Mothers at the Gampong Leuhan Integrated Health Post, Johan Pahlawan District, West Aceh Regency. Suggestions for Community Health Centers, especially the Gampong Leuhan Integrated Health Post, Johan Pahlawan District, West Aceh Regency, can use this research as information in improving the quality of services for mothers and children.